(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2022)
ABSTRACT This study was conducted in the poultry field of the department of animal production, college of agricultural engineering sciences, university of Baghdad for the period from 10/15/2021 to 11/25/2021 with the aim of showing the effect of adding different levels of dill seeds to the diet on productive and carcass traits For broiler meat. In this study, 200 unsexed broiler chicks of breed (Ross 308) were used, one day age, with a starting weight of 41.46 g. The chicks were randomly distributed to 5 treatments, and each treatment included 4 replicates, 10 birds for each replicate. The birds were fed three diets: the starter diet, the growth diet and the final diet. The experiment treatments were T1, T2, T3, T4 and T5, adding dill seeds at average 0, 0.3, 0.6, 0.9 and 1.2%, respectively. The results of the experiment indicated a significantly (P<0.05) excelled in cholesterol concentration at 42 d of age for treatment T4 compared with T2, and treatment T1 compared with treatment T2 in the level of triglycerides. Significantly excelled (P<0.05) was observed when calculating the high-density lipoproteins for the two treatments T3 and T4 compared with T5. Also, treatment T1 excelled on treatment T2 in the concentration of very low-density lipoproteins, and a significant decrease (P<0.01) in the level of MDA at 42 d of age was noted in favor of the addition treatments.